Drug utilization study in otorhinolaryngology outpatient department in a tertiary care teaching hospital - R., Sumalatha; H., Nagabushan; M., Hanumanth Prasad (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Drug utilization research is defined by the World Health Organization (WHO) as marketing, distribution, prescription, and use of drugs in society, with special emphasis on the resulting medical, social, and economic consequences. Drug utilization study identifies the problems that arise from prescription and highlights the current approaches to the rational use of drugs. The main aim of the study is to assess the pattern of drug usage and the rationality of drug use in Otorhinolaryngology out-patient department (OPD). Methods: A prospective observational study was conducted in the OPD of Otorhinolaryngology at tertiary care hospital, Mandya, Karnataka, over a period of one year. Prescriptions of all OPD patients were collected, relevant information entered in a specially designed proforma and analysed using descriptive statistics. Results: A total of 21058 drugs were prescribed out of 8028 prescriptions. Majority of the patients were male (51%). Antimicrobials were the most commonly prescribed drugs (28%), followed by antihistamines (25%), antipyretics (20.5%).Most of the drugs 18576 (88.2%) were prescribed by oral route, followed by topical route. Majority of the drugs were prescribed by the generic names (86.5%). Most common type of infection was ear infection (3176), followed by throat infection (2848) and nose infection (2004). Conclusions: The present study showed that among antimicrobial agents, β lactams were commonly prescribed drugs in the department of Otorhinolaryngology. The maximum number of cases was diagnosed with ear infections and majority of the drugs were prescribed orally.